A stroke service model developed in the private sector - Kow, Lynette K R (Division of Emergency Medicine, 2015)
This dissertation seeks primarily to enlighten the medical fraternity about the development of a stroke service at Constantiaberg Medi-Clinic and, additionally, how this has been implemented. The objective is to try to improve the outcome of patients presenting with various types and levels of neurological deficits as a consequence of cerebrovascular accidents.